Experimental Study of the Time of Reverberation of a Sacred Building Having a Cruciform Architecture. Issue 1 (January 2021) - Melnyk, M; Kernyskyy, A; Mykhalyna, Y; Pytel, K
Abstract: The response of the interior to the excitation of the pulse noise was registered using the Svan958A spectrum noise analyzer. After that, using the Dirac system, the registered files were analyzed and the time of reverberation of the church of St. John the Baptist, located in the village Verkhnya, Kalush district, Ivano-Frankivsk region, Ukraine with indication of measuring points. Detailed measurements of the investigated object were carried out and on their basis a 3D-model of the church in the SketchUP system was developed, which allowed to determine the recommended reverberation time for this type of interior and the given volume. The conducted researches made it possible to determine the uniformity of sound energy distribution in building having a cruciform architecture.